Rancang Bangun Visual Docking Guidance System (VDGS) Sebagai Pendeteksi Arah Gerak Longitudinal Pesawat Pada Sistem Parkir Pesawat Terbang - Denny Dermawan; Paulus Setiawan; Agus Basukesti; Riski Nur Muhammad (Aviation Electronics, Information Technology, Telecommunications, Electricals, Controls (AVITEC), 2021)
The growth of air transportation and technological developments is getting faster every year. This causes airport services to exceed the ability to provide facilities to meet growth adequately. In this case, it cannot be denied that there are always undesirable things that happen unexpectedly such as airplane accidents which are not only always in the air when flying, there are also many cases of plane accidents at the ground whether it's at the landing or parking process. Therefore, a Visual Docking Guidance System (VDGS) tool was designed using the TF Mini LiDAR sensor and programmed for the aircraft parking system at the airport to identify and guide pilots to find the right position when parking. This tool is able to give guidance information on the aircraft position.  A <<<< sign that is, the plane must move to the left, the >>>> sign, the plane must move to the right and the // \\ sign as an indicator the aircraft is in the middle position of parking stand. The results showed that the Visual Docking Guidance System (VDGS) using the LiDAR sensor with a distance specification of 10m is a fairly good level of accuracy and the error obtained from testing the distance measurement tool and actual distance has an error of 0-0,7368% with an average error of 0.0972%.